Implementasi Pembelajaran Responsif Gender di Madrasah Ibtidaiyah - Sholeh, Makherus (Pusat Studi Gender dan Anak - PSGA (Center for Gender and Child Studies) Institut Agama Islam Negeri Lhokseumawe, Aceh, 2023)
This study aims to understand the implementation of gender-responsive school programs in Madrasah Ibtidaiyah. The research method used was descriptive qualitative with research subjects including teachers and students. Data collection techniques consisted of observation, interviews and documentation, with data validity strengthened through triangulation of techniques. Data analysis adopted an interactive model. The results showed that the implementation of the gender-responsive school program in Madrasah Ibtidaiyah Swasta Al-Ashriyah Banjarmasin was carried out through three stages: habituation, intervention, and special activities. The implementation of the program in learning includes five aspects: classroom concepts that are in accordance with gender needs, gender-oriented lesson plans, learning resources that are accessible to men and women, learning media that are impartial to gender, and learning methods that provide equal opportunities for men and women. Gender-responsive school infrastructure includes lactation rooms for nursing mothers, equal distribution of bathrooms between men and women, and school health units that pay attention to the health needs of men and women. Supporting activities for gender-responsive school programs include routine activities such as women's studies and incidental activities such as gender-responsive school poster competitions, Dimas Diajeng, and student band competitions. Supporting factors from within the school include gender-responsive school management and gender-oriented learning, while factors from outside the school are support from the community and student guardians. This research provides an in-depth understanding of the implementation of gender-responsive school programs and the factors that support them, with the potential to improve gender equality in the educational environment. AbstrakPenelitian ini bertujuan untuk memahami implementasi program sekolah responsif gender di Madrasah Ibtidaiyah. Metode penelitian yang digunakan adalah deskriptif kualitatif dengan subjek penelitian meliputi guru dan siswa. Teknik pengumpulan data terdiri dari observasi, wawancara, dan dokumentasi, dengan keabsahan data diperkuat melalui triangulasi teknik. Analisis data mengadopsi model interaktif. Hasil penelitian menunjukkan bahwa implementasi program sekolah responsif gender di Madrasah Ibtidaiyah Swasta Al-Ashriyah Banjarmasin dilakukan melalui tiga tahap: pembiasaan, intervensi, dan kegiatan khusus. Implementasi program tersebut dalam pembelajaran mencakup lima aspek: konsep ruang kelas yang sesuai dengan kebutuhan gender, RPP berwawasan gender, sumber belajar yang dapat diakses oleh laki-laki dan perempuan, media pembelajaran yang tidak memihak gender, dan metode pembelajaran yang memberikan kesempatan yang sama bagi laki-laki dan perempuan. Sarana prasarana sekolah yang responsif gender mencakup ruang laktasi untuk ibu menyusui, pembagian kamar mandi yang seimbang antara laki-laki dan perempuan, dan unit kesehatan sekolah yang memperhatikan kebutuhan kesehatan laki-laki dan perempuan. Kegiatan penunjang program sekolah responsif gender meliputi kegiatan rutin seperti kajian keputrian dan kegiatan insidental seperti lomba poster sekolah responsif gender, Dimas Diajeng, dan lomba band peserta didik. Faktor pendukung dari dalam sekolah meliputi manajemen sekolah yang responsif gender dan pembelajaran berwawasan gender, sementara faktor dari luar sekolah adalah dukungan dari masyarakat dan wali murid. Penelitian ini memberikan pemahaman yang mendalam tentang implementasi program sekolah responsif gender dan faktor-faktor yang mendukungnya, dengan potensi untuk meningkatkan kesetaraan gender di lingkungan pendidikan.